Hyperbranched anion exchange magnetic solid-phase extraction adsorbent as well as preparation method and application thereof
Through the preparation and application of hyperbranched anion exchange magnetic solid-phase extraction adsorbent, the low selectivity and insufficient sensitivity of cannabinoid detection in wastewater are solved, and the rapid and accurate extraction and trace analysis of cannabinoids are achieved, which simplifies the detection process .
Patent Information
- Application Number
- CN202411293488.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems such as low selectivity, insufficient sensitivity and difficulty in detecting trace analytes in complex samples in cannabinoid detection in wastewater, especially due to the high lipophilicity of cannabinoids, resulting in low extraction efficiency and analytes are easily adsorbed by the matrix. .
Ultrasonic pulverization and condensation reaction were carried out by using hyperbranched anion exchange magnetic solid phase extraction adsorbent, and Fe3O4 microspheres modified with oleic acid and glycidyl methacrylate and divinylbenzene to form Fe3O4@poly(GMA/ DVB-WAX microspheres were modified by ethylenediamine and 1,4-butanediol glycidyl ether to prepare a hyperbranched anion exchange magnetic solid-phase extraction adsorbent, combined with external magnets for adsorption and elution, realizing cannabinoids Quick extraction.
This adsorbent realizes the selective extraction of cannabinoids through various mechanisms of action, simplifies the pretreatment steps, improves analysis efficiency and sensitivity, and can quickly and accurately detect four major cannabinoids in sewage, meeting the requirements of trace analysis .
Smart Images

Figure CN119186497A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of illegal drug detection and relates to a novel adsorbent, in particular to a hyperbranched anion exchange magnetic solid phase extraction adsorbent and a preparation method and application thereof. Background Art
[0002] At present, marijuana is the most consumed drug in the world. Marijuana is addictive, and long-term use will pose a serious threat to human health. Cannabinoids extracted from cannabis plants can directly act on the brain's cannabis receptors. The main components are tetrahydrocannabinol (THC), cannabidiol (CBD), cannabinol (CBN), etc. THC is the main psychoactive ingredient in marijuana. It is a highly lipophilic viscous oil with hallucinogenic and analgesic effects. CBD is not psychoactive and is usually used for pharmacological purposes such as anti-inflammatory, anti-anxiety and anti-epileptic. Cannabinoids can enter the human body through three routes: inhalation, oral administration and skin ingestion. When the human body ingests cannabinoids, the psychoactive ingredient THC enters the blood and is metabolized by the liver into 11-hydroxy-Δ9-tetrahydrocannabinol (THC-OH), which is then converted into the main metabolite tetrahydrocannabinolic acid (THC-COOH). THC-COOH is excreted from the human body's urine or feces in the form of glucuronic acid conjugates. After sewage treatment, bacteria in the excreta can easily hydrolyze it into the form of free acid, namely THC-COOH. Therefore, THC-COOH is identified by many researchers as a biomarker for cannabinoid use and has become the main monitoring indicator for cannabinoids in sewage epidemiology (WBE).
[0003] The detection of cannabinoids and their metabolites in sewage has always been a difficult problem and challenge faced by researchers. This is because cannabinoids are highly lipophilic and are easily adsorbed by the matrix, so the concentration in sewage is extremely low. At present, the commonly used extraction methods for cannabinoids in sewage are liquid-liquid extraction and solid-phase extraction. Liquid-liquid extraction has disadvantages such as low selectivity and insufficient sensitivity, and cannot meet the detection concentration requirements of cannabinoids in sewage. The column solid-phase extraction process involves steps such as sample collection, filtration and solid-phase extraction loading. These operations increase the possibility of cannabinoid analytes being adsorbed in other experimental equipment or matrices, seriously affecting the extraction recovery rate. Magnetic solid-phase extraction (MSPE) uses magnetic nanoparticles as adsorbents, and can directly extract target analytes from large-volume samples under the action of an external magnetic field. Compared with liquid-liquid extraction and solid-phase extraction, MSPE can complete the purification, separation and concentration of target compounds in one step, simplify the pretreatment steps, and improve the analysis efficiency, so it has more advantages. In terms of adsorbent type, most of the Oasis HLB adsorbents used for the extraction of cannabinoids in sewage are used, and its adsorption mechanism for cannabinoids is reverse phase action. However, reversed-phase reaction alone has low selectivity in retaining target analytes, especially when matrix effects caused by co-extraction are at a high level, which can result in the analytical method being unable to meet the detection requirements of trace analytes in complex samples. Summary of the invention
[0004] The purpose of the present invention is to provide a hyperbranched anion exchange magnetic solid phase extraction adsorbent to address the deficiencies of the prior art, which can be used to quickly extract cannabinoids from wastewater. The present invention also provides a preparation method of the hyperbranched anion exchange magnetic solid phase extraction adsorbent and its application in the extraction of cannabinoids from wastewater.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] A method for preparing a hyperbranched anion exchange magnetic solid phase extraction adsorbent comprises the following steps:
[0007] 1) Take oleic acid-modified Fe3O4 microsphere material OA-Fe3O4, glycidyl methacrylate (GMA), divinylbenzene (DVB) and porogen cyclohexane and mix them evenly to obtain solution A, take polyvinyl alcohol 1788 and sodium chloride and dissolve them in water and mix them evenly to obtain solution B, mix solution A and solution B, and grind them by ultrasonication under ice bath conditions. When there is no obvious oil layer on the surface of the solution and it is in a uniform emulsion state, stop ultrasonication, transfer the mixed solution to a three-necked flask equipped with a mechanical stirrer, introduce nitrogen before the reaction is heated to exclude air in the reaction environment, and after the air is excluded, add potassium persulfate (K2S2O8) as an initiator to the reaction solution to carry out condensation reflux reaction, and continuously introduce nitrogen during the reaction. After the reaction is completed, the obtained magnetic microspheres Fe3O4@poly(GMA / DVB) are washed alternately for multiple times with ethanol and deionized water by external magnet adsorption until the top of the solution is clear and free of suspended matter;
[0008] 2) Hyperbranched modification:
[0009] (a) The Fe3O4@poly(GMA / DVB) obtained in the previous step is dispersed in an isopropanol solution, and then ethylenediamine (EDA) is added. The solution is ultrasonically mixed and stirred for reaction. After the reaction is completed, the magnetic microspheres are washed with ethanol and ultrapure water for multiple times.
[0010] (b) dispersing the magnetic microspheres after the reaction again in an isopropanol solution, adding 1,4-butanediol glycidyl ether (BDDGE), mixing the solution by ultrasonication and stirring for reaction, and after the reaction is completed, washing the magnetic microspheres after the reaction with ethanol and ultrapure water for multiple times;
[0011] (c) Repeat step (a) again, wash the reacted material with ultrapure water and ethanol in turn, and then dry it to obtain hyperbranched modified mixed mode anion exchange magnetic microspheres Fe3O4@poly (GMA / DVB-WAX), that is, obtain a hyperbranched anion exchange magnetic solid phase extraction adsorbent.
[0012] In the above technical solution, further, the preparation method of the oleic acid modified Fe3O4 microsphere material OA-Fe3O4 is as follows:
[0013] Dissolve FeCl3·6H2O in ethylene glycol, add sodium acetate and polyethylene glycol 4000, heat to dissolve, transfer the obtained mixture to a reactor, and heat to react; after the reaction is completed, put the obtained Fe3O4 material into oleic acid, heat and stir to react, and then wash it repeatedly with water and ethanol several times to obtain OA-Fe3O4. The usage ratio of FeCl3·6H2O, ethylene glycol, sodium acetate and polyethylene glycol 4000 can usually be 2.0g:60mL:5.4g:1.5g.
[0014] Furthermore, the usage ratio of OA-Fe3O4, GMA, DVB and cyclohexane in the solution A can generally be 0.5 g: (1.5-2.5) mL: (0.5-1.5) mL: (0.5-1.5) mL.
[0015] Furthermore, the mass ratio of polyvinyl alcohol 1788 to sodium chloride in the solution B is usually 1:5.
[0016] Furthermore, the volume ratio of solution A to solution B is generally (2.5-5.5):150.
[0017] Furthermore, the temperature of the condensation reflux reaction is 70° C., the stirring rate is 150 r / min, and the reaction time is 6-12 h.
[0018] Furthermore, the stirring reaction has a stirring rate of 150-250 r / min, a reaction temperature of 65-75° C., and a reaction time of 2-3 h.
[0019] The hyperbranched anion exchange magnetic solid phase extraction adsorbent is used in the detection of cannabinoids in sewage, wherein the cannabinoids are one or more of tetrahydrocannabinol (THC), cannabidiol (CBD), cannabinol (CBN), and tetrahydrocannabinolic acid (THC-COOH); during the detection, the pH of the sewage sample is first adjusted to neutral, and then 30 mg of the hyperbranched anion exchange magnetic solid phase extraction adsorbent is dispersed into 40-400 mL of the sewage sample, fully stirred and ultrasonically dispersed for at least 30 seconds, adsorbed for 5-20 minutes, and then the adsorbent is collected with an external magnet. Then, impurities are removed with a detergent, and the adsorbed cannabinoids are eluted with an eluent to separate the cannabinoids from the sewage sample.
[0020] In this detection scheme, the adsorbent can be activated using 3 mL of 8% ammonia / methanol (NH3H2O / MeOH) and ultrapure water in sequence before being dispersed into the sewage sample.
[0021] The pH of the sewage sample can be adjusted to 4-10, preferably 6-7.
[0022] The washing agent is usually 5% MeOH / H2O, 10% MeOH / H2O, ACN or MeOH, and the eluting agent is usually 8% HCOOH / MeOH, 8% HCOOH / ACN, or 8% NH3.H2O / MeOH.
[0023] The percentage indicates the volume concentration of the component before the slash in the component after it.
[0024] After the cannabinoids are separated from the sewage samples by the above method to achieve the selective extraction of cannabinoids, an isotope internal standard quantitative method for the detection of four cannabinoids in sewage can be established in combination with ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS / MS) to perform qualitative and quantitative analysis of the four cannabinoids in sewage.
[0025] The beneficial effects of the present invention are:
[0026] The hyperbranched anion exchange magnetic solid phase extraction adsorbent provided by the present invention has a simple preparation method, low cost and easy use. It is applied to the field of cannabinoid detection in sewage, and can quickly extract four main cannabinoids from sewage: tetrahydrocannabinol, cannabidiol, cannabinol and tetrahydrocannabinic acid. Compared with the common commercial Oasis MCX adsorbent and Oasis HLB adsorbent, this adsorbent has better extraction efficiency. Compared with the common column solid phase extraction method, this adsorbent adopts a magnetic solid phase extraction method, which can directly extract the sample without filtering, simplifying the pretreatment steps and improving the sensitivity of the method. This adsorbent establishes reverse phase and ion exchange effects between the polymer skeleton and the anion exchange group and the cannabinoid, and realizes the selective extraction of cannabinoids through the comprehensive effects of hydrophobic action, electrostatic action, π-π stacking action and hydrogen bonding action. An isotope internal standard quantitative method for the detection of four cannabinoids in sewage was established in combination with ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS / MS). This method has the advantages of short pretreatment time, simple operation, sensitivity and accuracy, and can meet the requirements of trace analysis of the four cannabinoids in actual sewage samples. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 These are SEM micrographs of (a) Fe3O4 and (b) Fe3O4@poly(GMA / DVB-WAX) samples in Example 1.
[0028] Figure 2 This is the EDS graph of the Fe3O4@poly(GMA / DVB-WAX) sample in Example 1.
[0029] Figure 3 It is the infrared spectra of OA-Fe3O4, Fe3O4@poly(GMA / DVB) and Fe3O4@poly(GMA / DVB-WAX) in Example 1.
[0030] Figure 4 This is the XPS spectrum of the Fe3O4@poly(GMA / DVB-WAX) sample in Example 1.
[0031] Figure 5Optimization of the magnetic solid phase extraction procedure in Example 2, (a) the effect of detergent on the recovery rate, (b) the effect of eluent on the recovery rate.
[0032] Figure 6 (a) Comparison of extraction efficiency of three adsorbents in Example 3, and (b) comparison of magnetic solid phase extraction and column solid phase extraction methods.
[0033] Table 1 shows the corresponding parameters of the internal standard quantitative method in Example 4.
[0034] Table 2 shows the recovery and precision results of the method in Example 4.
[0035] Table 3 shows the spiked recoveries of the simulated positive samples in Example 4. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.
[0037] Example 1
[0038] 1) Dissolve FeCl3·6H2O in ethylene glycol, add sodium acetate and polyethylene glycol 4000, heat to dissolve, transfer the obtained mixture to a reactor, and heat to react; after the reaction is completed, put the obtained Fe3O4 material into oleic acid, heat and stir to react, and then wash it repeatedly with water and ethanol several times to obtain OA-Fe3O4; 2) Take 0.5g of OA-Fe3O4, 2mL of glycidyl methacrylate (GMA), 1mL of divinylbenzene (DVB) and 1mL of porogen cyclohexane to prepare mixed solution A, and ultrasonically homogenize it. Then take 0.3g of polyvinyl alcohol 1788 and 1.5g of sodium chloride and dissolve them in 150mL of aqueous solution to prepare solution B, and ultrasonically dissolve it. After solution B is completely mixed, mix solution A and solution B, place them in an ultrasonic cell crusher, and ultrasonically crush them under ice bath conditions (ultrasonic power 200W). When there is no obvious oil layer on the surface of the solution and it presents a uniform emulsion state, stop ultrasonication. Transfer the ultrasonic mixed solution to a three-necked flask equipped with a mechanical stirrer. Before the reaction is heated up, nitrogen is introduced for 30 minutes to remove the air in the reaction environment. After the air is removed, 0.08g of potassium persulfate (K2S2O8) is added to the reaction solution as an initiator. Then the reaction temperature is set to 70°C for condensation reflux reaction. The stirring rate is 150r / min, and nitrogen is continuously introduced during the reaction. After 8 hours of reaction, the obtained product Fe3O4@poly(GMA / DVB) magnetic microspheres are alternately washed several times with ethanol and deionized water by external magnet adsorption until the solution is clear and free of suspended matter. Finally, the cleaned Fe3O4@poly(GMA / DVB) is dispersed in an ethanol solvent and stored for later use;
[0039] 3) Hyperbranched modification: (a) Disperse Fe3O4@poly(GMA / DVB) in 60mL isopropanol solution, then add 2mL of ethylenediamine (EDA), mix the solution by ultrasonication, transfer it to a three-necked flask and stir for 2h, the stirring rate is 200r / min, the reaction temperature is 70℃, after the reaction is completed, wash the magnetic microspheres after the reaction with ethanol and ultrapure water several times. (b) Disperse the magnetic microspheres after the reaction again in 60mL isopropanol solution, add 3mL of 1,4-butanediol glycidyl ether (BDDGE), mix the solution by ultrasonication, transfer it to a three-necked flask and stir for 2h, the stirring rate is 200r / min, the reaction temperature is 70℃, after the reaction is completed for 2h, wash the magnetic microspheres after the reaction with ethanol and ultrapure water several times. (c) Repeat step (a) again, wash the reacted material with ultrapure water and ethanol in turn, and dry it in a vacuum drying oven at 50℃ for 24h. Finally, the hyperbranched modified mixed mode anion exchange magnetic microspheres Fe3O4@poly(GMA / DVB-WAX) were obtained. The SEM micrograph is shown in Figure 1As shown, EDS diagram is as follows Figure 2 As shown, FT-IR spectrum is as Figure 3 As shown in the XPS spectrum Figure 4 shown.
[0040] Example 2
[0041] 1) Accurately weigh 30 mg of magnetic solid phase extraction adsorbent Fe3O4@poly (GMA / DVB-WAX), and activate the adsorbent with 3 mL 8% NH3H2O / MeOH and ultrapure water in turn. The concentrations of the four cannabinoid standards THC, CBD, CBN, and THC-COOH in the sample solution are all 200 ng / L. The pH value of the sample solution is adjusted to 7, and then the activated magnetic solid phase extraction adsorbent is dispersed in 200 mL of the sample solution for adsorption extraction. The extraction process is continuously stirred and ultrasonically dispersed for 30 seconds. The entire adsorption time is 5 minutes. After the adsorption is completed, the magnetic adsorbent is separated from the sample solution by external magnet adsorption.
[0042] 2) The magnetic material after separation was transferred to a 10 mL glass centrifuge tube for washing, and 3 mL of detergent (5% MeOH / H2O, 10% MeOH / H2O, ACN, or MeOH) was added and vortexed for 30 seconds to remove interfering impurities through the washing step. The effects of different detergents on the extraction recovery rate were investigated, such as Figure 5 (a) When 5% MeOH / H2O was used as the washing solvent, the recovery rate of the four analytes was the best.
[0043] 3) After washing, the analyte was eluted. 4 mL of eluent (8% HCOOH / MeOH, 8% HCOOH / ACN, or 8% NH3·H2O / MeOH) was divided into two batches for elution, each with a volume of 2 mL. The eluted solution was collected in a 10 mL glass test tube for nitrogen enrichment. Nitrogen was blown at room temperature. When the eluent was blown to near dryness, 200 μL of 0.2% HCOOH / MeOH solution was used to re-dissolve the eluted analyte, and then filtered using a 0.22 μm pore size aqueous needle filter membrane. Finally, the filtered solution was transferred to a liquid injection vial for UHPLC-MS / MS analysis. The results are shown in Figure 5 As shown in (b), considering the recoveries of the four analytes THC, CBD, CBN and THC-COOH, the recovery effect was better when using 8% HCOOH / MeOH as the elution solvent.
[0044] Example 3
[0045] 1) Fe3O4@poly(GMA / DVB-WAX) magnetic solid phase adsorbent was compared with the commonly used Oasis HLB and Oasis MCX column solid phase extraction adsorbents to investigate the adsorption efficiency of four cannabinoids: THC, CBD, CBN and THC-COOH. Take 200mL of ultrapure water and add the mixed standard solution of the four cannabinoids to the water at a concentration of 200ng / L. The extraction recovery results are shown in Figure 6 As shown in (a), the extraction recovery rates of the four cannabinoids by Fe3O4@poly(GMA / DVB-WAX) were between 67.1% and 95.7%, which were significantly higher than those of Oasis MCX and Oasis HLB.
[0046] 2) Considering that column-based solid-phase extraction often requires glass fiber membrane filtration of water samples before the extraction step (to remove insoluble suspended particles in the water sample, ensure the purity of the water sample, and avoid these particles interfering with the adsorption and elution of the target compound in the subsequent solid-phase extraction process. Filtration through glass fiber membranes can effectively remove large particle impurities in the water sample and avoid clogging the membrane), the samples filtered through glass fiber membranes are subjected to column-based solid-phase extraction, while magnetic solid-phase extraction does not require membrane filtration. The sample is directly extracted and adsorbed after only being transferred through glassware. The same as in 1), but for the column-based solid-phase extraction method, the spiked water sample is filtered with a 0.45μm glass fiber membrane before sample extraction, and the filtrate is collected before the solid-phase extraction step. Magnetic solid-phase extraction does not require membrane filtration. The sample is directly extracted and adsorbed after only being transferred through glassware. The remaining steps are the same as the column-based solid-phase extraction method. The recovery results of the two methods are compared, as shown in Figure 6 As shown in (b). It was found that after the samples were filtered through the glass fiber membrane, the extraction recovery rates of Oasis MCX and Oasis HLB decreased significantly. The extraction recovery rate of THC-COOH in Oasis HLB decreased from 40.7% before the membrane to 27.9%, and the extraction recovery rate of CBD decreased from 17.6% to 8.5%. The results of the extraction recovery rate of magnetic solid phase extraction did not change significantly. The above results also indicate that during the filtration process of the sample, the glass fiber membrane and the four cannabinoid analytes were adsorbed.
[0047] Therefore, Fe3O4@poly(GMA / DVB-WAX) as a magnetic solid phase extraction adsorbent has obvious advantages over conventional Oasis MCX and Oasis HLB solid phase extraction methods both in terms of operation method and adsorption efficiency.
[0048] Example 4
[0049] 1) The isotope internal standard quantitative method was used for the qualitative and quantitative analysis of four cannabinoids in sewage, and the linear range, detection limit, quantification limit, accuracy and reproducibility of the method were evaluated. The relevant validation parameters of the internal standard quantitative method are shown in Table 1. The sensitivity of the method was evaluated by the method detection limit (LODs) and quantification limit (LOQs). The LODs and LOQs of the four cannabinoids were 0.17-0.33 ng / L and 0.5-1 ng / L, respectively. The relationship between the peak area and the analyte concentration obtained by UHPLC-MS / MS analysis was used to prepare the internal standard curves of the four analytes. The linear ranges of THC, CBN and THC-COOH were 0.5-100 ng / L, and the linear range of CBD was 1-100 ng / L. The linear correlation coefficients r2 of all target compounds were greater than 0.9962. The accuracy of the method was investigated by the spike recovery experiment. Three concentration levels of low, medium and high within the linear range were selected for the spike recovery experiment, as shown in Table 2. Finally, the spike recovery of the four cannabinoids was between 94.3% and 101.8%. At the same time, the stability and reproducibility of the method were investigated by intra-day precision (n=6) and inter-day precision (n=3). Using relative standard deviations (RSDs), it can be seen that the intra-day precision and inter-day precision are less than 11.2% and 7.9%, respectively. The above results show that the established analytical method has a low detection limit and good linearity, and has good accuracy and reproducibility, which meets the requirements of relevant standards. The sensitivity and accuracy of the method can meet the detection requirements of the four cannabinoids THC, CBN, CBD, and THC-COOH in sewage.
[0050] Table 1
[0051]
[0052] Table 2
[0053]
[0054]
[0055] In order to further evaluate the applicability of Fe3O4@poly(GMA / DVB-WAX) adsorbent, it was applied to real sewage samples for detection and analysis. The spike recovery experiment was carried out by simulating positive samples. The results are shown in Table 3. It can be seen that the spike recovery rates of the four cannabinoids are between 85.8% and 106.5%, which shows that the method has good accuracy and practicality.
[0056] Table 3
[0057]
[0058] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A method for preparing a hyperbranched anion exchange magnetic solid phase extraction adsorbent, characterized in that: The steps include: 1) Take oleic acid-modified Fe3O4 microsphere material OA-Fe3O4, glycidyl methacrylate (GMA), divinylbenzene (DVB) and porogen cyclohexane and mix them evenly to obtain solution A, take polyvinyl alcohol 1788 and sodium chloride and dissolve them in water and mix them evenly to obtain solution B, mix solution A and solution B, and grind them by ultrasonication under ice bath conditions. When there is no obvious oil layer on the surface of the solution and it is in a uniform emulsion state, stop ultrasonication, transfer the mixed solution to a three-necked flask equipped with a mechanical stirrer, introduce nitrogen before the reaction is heated to exclude air in the reaction environment, and after the air is excluded, add potassium persulfate (K2S2O8) as an initiator to the reaction solution to carry out condensation reflux reaction, and continuously introduce nitrogen during the reaction. After the reaction is completed, the obtained magnetic microspheres Fe3O4@poly(GMA / DVB) are washed alternately for multiple times with ethanol and deionized water by external magnet adsorption until the top of the solution is clear and free of suspended matter; 2) Hyperbranched modification: (a) The Fe3O4@poly(GMA / DVB) obtained in the previous step is dispersed in an isopropanol solution, and then ethylenediamine (EDA) is added. The solution is ultrasonically mixed and stirred for reaction. After the reaction is completed, the magnetic microspheres are washed with ethanol and ultrapure water for multiple times. (b) dispersing the magnetic microspheres after the reaction again in an isopropanol solution, adding 1,4-butanediol glycidyl ether (BDDGE), mixing the solution by ultrasonication and stirring for reaction, and after the reaction is completed, washing the magnetic microspheres after the reaction with ethanol and ultrapure water for multiple times; (c) Repeat step (a) again, wash the reacted material with ultrapure water and ethanol in turn, and then dry it to obtain hyperbranched modified mixed mode anion exchange magnetic microspheres Fe3O4@poly (GMA / DVB-WAX), that is, obtain a hyperbranched anion exchange magnetic solid phase extraction adsorbent.
2. The method for preparing a hyperbranched anion exchange magnetic solid phase extraction adsorbent according to claim 1, characterized in that: The preparation method of the oleic acid-modified Fe3O4 microsphere material OA-Fe3O4 is as follows: FeCl3·6H2O was dissolved in ethylene glycol, sodium acetate and polyethylene glycol 4000 were added, and the mixture was heated to dissolve. The obtained mixture was transferred to a reactor and heated to react. After the reaction was completed, the obtained Fe3O4 material was placed in oleic acid, heated and stirred for reaction, and then washed repeatedly with water and ethanol for several times to obtain OA-Fe3O4.
3. The method for preparing a hyperbranched anion exchange magnetic solid phase extraction adsorbent according to claim 1, characterized in that: The dosage ratio of OA-Fe3O4, GMA, DVB and cyclohexane in the solution A is 0.5 g: (1.5-2.5) mL: (0.5-1.5) mL: (0.5-1.5) mL.
4. The method for preparing a hyperbranched anion exchange magnetic solid phase extraction adsorbent according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol 1788 to sodium chloride in the solution B is 1:
5.
5. The method for preparing a hyperbranched anion exchange magnetic solid phase extraction adsorbent according to claim 1, characterized in that: The volume ratio of solution A to solution B is (2.5-5.5):
150.
6. The method for preparing a hyperbranched anion exchange magnetic solid phase extraction adsorbent according to claim 1, characterized in that: The temperature of the condensation reflux reaction is 70° C., the stirring rate is 150 r / min, and the reaction time is 6-12 h.
7. The method for preparing a hyperbranched anion exchange magnetic solid phase extraction adsorbent according to claim 1, characterized in that: The stirring reaction has a stirring rate of 150-250 r / min, a reaction temperature of 65-75° C., and a reaction time of 2-3 h.
8. A hyperbranched anion exchange magnetic solid phase extraction adsorbent, characterized in that: The method is prepared by the method according to any one of claims 1 to 7.
9. The use of the hyperbranched anion exchange magnetic solid phase extraction adsorbent as claimed in claim 8 in the detection of cannabinoids in sewage, characterized in that: The cannabinoids are one or more of tetrahydrocannabinol (THC), cannabidiol (CBD), cannabinol (CBN), and tetrahydrocannabinolic acid (THC-COOH); during detection, the pH of the sewage sample is first adjusted to neutral, and then 30 mg of the hyperbranched anion exchange magnetic solid phase extraction adsorbent is dispersed into 40-400 mL of the sewage sample, fully stirred and ultrasonically dispersed for at least 30 seconds, adsorbed for 5-20 minutes, and then the adsorbent is collected with an external magnet. Then, impurities are removed with a detergent, and the adsorbed cannabinoids are eluted with an eluent to separate the cannabinoids from the sewage sample.
10. The use according to claim 9, characterized in that: The washing agent is 5% MeOH / H2O, 10% MeOH / H2O, ACN or MeOH, and the eluent is 8% HCOOH / MeOH, 8% HCOOH / ACN, or 8% NH3·H2O / MeOH.
Citation Information
Patent Citations
Preparation method and application of dendrimer macromolecule-modified polymer with reversed phase / strong anion exchange mixed mode
CN109851801A
Magnetic nano adsorption material as well as preparation method and application thereof
CN117358195A
Mixed-mode weak cation exchange magnetic solid-phase extraction adsorbent as well as preparation method and application thereof
CN117504833A
Cited By
Method for analyzing liver injury treatment mechanism of YZH based on network pharmacology
CN121122377A
